Long term bed rest with and without vibration exercise countermeasures: Effects on human muscle protein dysregulation - Moriggi, Manuela; Vasso, Michele; Fania, Chiara; Capitanio, Daniele; Bonifacio, Gaetano; Salanova, Michele; Blottner, Dieter; Rittweger, Jörn; Felsenberg, Dieter; Cerretelli, Paolo; Gelfi, Cecilia (Proteomics (Weinheim), 2010)
The present investigation, the first in the field, was aimed at analyzing differentially, on individual samples, the effects of 55 days of horizontal bed rest, a model for microgravity, on myosin heavy and myosin light chain isoforms distribution (by SDS) and on the proteome (by 2‐D DIGE and MS) in the vastus lateralis (VL), a mixed type II/I (∼50:50%) head of the quadriceps and in the calf soleus (SOL), a predominantly slow (∼35:65%) twitch muscle. Two separate studies were performed on six subjects without (BR) and six with resistive vibration exercise (RVE) countermeasures, respectively. Both VL and SOL underwent in BR decrements of ∼15% in cross‐sectional area and of ∼22% in maximal torque that were prevented by RVE. Myosin heavy chain distribution showed increased type I and decreased type IIA in BR both in VL and in SOL, the opposite with RVE. A substantial downregulation of proteins involved in aerobic metabolism characterized both in SOL and VL in BR. RVE reversed the pattern more in VL than in SOL, whereas proteins involved in anaerobic glycolysis were upregulated. Proteins from the Z‐disk region and from costamers were differently dysregulated during bed rest (both BR and RVE), particularly in VL.